PERANCANGAN ALAT PEMBERIAN PUPUK CAIR PADA TANAMAN BUNGA KATSUBA OTOMATIS MENGGUNAKAN NODEMCU BERBASIS INTERNET OF THINGS (IOT) (STUDI KASUS : RIKI FLORA) - Sufriyah; Devi Yunita (CV. Multi Kreasi Media, 2023)
The provision of fertilizer on katsuba plants carried out by katsuba plant farmers on average is still carried out directly, where katsuba plant farmers must bring a container that already contains fertilizer and then pour it on the plants one by one. This may not be a problem for farmers who have free time, but for katsuba plant farmers who have other activities or are far away, this becomes a problem for plant owners because when a katsuba plant is not given the required fertilizer, it causes the plant can not develop properly. Therefore, we need a tool that can provide liquid fertilizer in order to help plant owners in the process of giving liquid fertilizer to katsuba flower plants. The liquid fertilizer application that will be made can be used for automatic fertilization of plants. The method used is the waterfall method. The waterfall method is serial in nature starting from the planning, analysis, design, and implementation processes on the system. This automatic liquid fertilizer application for katsuba flower plants functions to provide liquid fertilizer to katsuba plants automatically using the ESP8266 nodemcu and can be accessed remotely using the Blynk application which functions to set the schedule for fertilizer application. This tool is also equipped with the concept of the Internet of Things (IoT) which will be connected to each other so that it is easy to use and can monitor directly by opening a web server/application that is already connected with internet access about the timing of fertilizer application in the plant area.